Representasi Dampak Psikologis Kekerasan Seksual terhadap Anak: Studi Kasus Cerpen Azul Maya karya Laksmi Pamuntjak dalam Antologi Kitab Kawin - Novela, Windi; Wartiningsih, Agus; Mariyadi, Mariyadi (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Studies on sexual violence in Indonesian literature are still limited to the socio-cultural aspects, while the representation of the psychological impact on child victims has not been widely examined. This article fills this gap by analyzing the short story Azul Maya by Laksmi Pamuntjak from the anthology Kitab Kawin, with a focus on the trauma of child victims of incest. This research is limited to one short story to explore the complexity of the main character's psychological experience. Using a literary psychology approach, descriptive qualitative method, and thematic analysis, the research found trauma symptoms in the form of anger, anxiety, fear, and depression reflected in emotional changes, withdrawn behavior, eating disorders, and dissociation. This representation reveals trauma as a structural impact of sexual violence in a patriarchal system. The findings affirm the function of literature as an aesthetic medium as well as social critique, and expand the interdisciplinary contributions between literature and psychology.